Comprehensive analysis of cutaneous adverse drug reactions during hospitalization: unveiling nuanced complexities and ensuring patient safety - Junaid Ahmad Ahangar; Semira; Seema Qayoom; Mudasir Shafi Bhat (Creative Pharma Assent, 2024)
Background: The spectrum of cutaneous drug reactions encompasses a broad range from benign rashes to potentially life-threatening conditions. The present study aims to comprehensively investigate the frequency, type, causality, preventability, and severity of adverse drug reactions (CADRs) occurring during hospitalization. Methods:  Conducted at SKIMS Medical College Hospital over a comprehensive six-month duration, this study systematically monitored the occurrence of cutaneous drug reactions. These reactions' causality, severity, and preventability assessments were meticulously conducted using established classifications such as the Wills and Brown classification, WHO criteria, Hartwig scale, and modified Schumock and Thornton scales. Result and discussion: Involving a cohort of 300 admissions, the study identified an incidence of adverse drug reactions (CADRs) at 8%. Detailed analysis revealed no significant associations between CADRs and gender, drug allergy history, or the number of drugs administered. Notably, Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), particularly Dapsone, emerged as the most common drug class associated with cutaneous adverse drug reactions (CADRs), accounting for 41.67% of cases.  Antibiotics, including linezolid (12.5%) and amikacin (12.5%), followed closely. Itching (37.5%), followed by red raised lesions (33.33%), emerged as the predominant reported reactions, showcasing associations with various drugs. Notably, a significant proportion of CADRs were categorized as mild (50%), with 95.83% deemed not preventable. Conclusion:  The prevalence of mild reactions, particularly linked to NSAIDs and antibiotics, underscores the nuanced complexities in drug responses. The research enriches the broader comprehension of adverse drug reactions, underscoring the imperative for meticulous surveillance and scholarly inquiry to elevate patient safety.